THE GRIEF AND TRAUMA PROJECT: A GROUP WORK APPROACH TO RESTORING EMOTIONAL AND SPIRITUAL HEALTH TO WOMEN IN BEREAVED AND TRAUMATISED INDIGENT COMMUNITIES IN THE WESTERN CAPE, SOUTH AFRICA - McLea, Hilary; Mayers, Pat (Social Work/Maatskaplike Werk, 2017)
The extreme levels of grief and trauma experienced in resource-poor communities in South Africa are well documented. The concept of grief or trauma being experienced and managed as an isolated incident and access to psychological therapeutic support being available is assumed in much of Western literature. This study describes a response to the multiple grief and loss experiences of indigent South African communities, its continual nature and the paucity of help available. A group work approach to providing psychosocial and spiritual support was developed and implemented. Improved mental health, physical health and interpersonal relationship outcomes are described.